1999
DOI: 10.1046/j.1460-9568.1999.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the corpus callosum in the somatosensory activation of the ipsilateral cerebral cortex: an fMRI study of callosotomized patients

Abstract: To verify whether the activation of the posterior parietal and parietal opercular cortices to tactile stimulation of the ipsilateral hand is mediated by the corpus callosum, a functional magnetic resonance imaging (fMRI, 1.0 tesla) study was performed in 12 control and 12 callosotomized subjects (three with total and nine with partial resection). Eleven patients were also submitted to the tactile naming test. In all subjects, unilateral tactile stimulation provoked a signal increase temporally correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 86 publications
9
50
0
Order By: Relevance
“…1). Two of these patients (DDV, RN) had participated in a previous study (Fabri et al, 1999a). The clinical history and extent of callosal resection of all patients have been reported previously Quattrini et al, 1989Quattrini et al, , 1994Fabri et al, 1999a).…”
Section: Methodsmentioning
confidence: 84%
“…1). Two of these patients (DDV, RN) had participated in a previous study (Fabri et al, 1999a). The clinical history and extent of callosal resection of all patients have been reported previously Quattrini et al, 1989Quattrini et al, , 1994Fabri et al, 1999a).…”
Section: Methodsmentioning
confidence: 84%
“…59,60 The sensory cortical representations are interhemispherically linked to their homotopic counterparts in the opposite hemisphere via fibers that traverse the corpus callosum. [61][62][63] This pathway is usually inhibited under normal circumstances but could be disinhibited in the presence of a unilateral stroke. 64 A previous study indicated that inhibition of the transcallosal pathway is reduced in the event of a unilateral focal stroke.…”
Section: Bilateral Forepaw Stimulation Results In Better Outcome Thanmentioning
confidence: 99%
“…The lesser recruitment of these areas over time suggests that recourse to such strategies becomes less necessary with time, in parallel with motor recovery. In normal subjects, the bilateral activation of BA 40 has been related to transcallosal connections, 33 which may therefore be involved during motor recovery.…”
Section: Discussionmentioning
confidence: 99%